Technical Efficiency of Manufacturing Enterprises in Libya: A Stochastic Frontier Analysis (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This paper examines the performance of manufacturing firms in Libya. Specifically, it evaluates firm level technical efficiency. The paper uses an econometric approach based on a stochastic frontier production function to analyze 207 firms from survey conducted from March to May 2013. The results from estimations reveal that technical efficiencies of Libyan manufacturing firms ranging from 37.77 percent to 95.27 percent, with an average of 71.27 percent. While, the percent of firms that considered technically efficient is only 17.87 percent of the total firms.